Clinical writing in neuropsychoanalysis. Issue 2 (3rd July 2022) - Flores Mosri, Daniela; Abrams, Jane; Barry, Virginia; Biran, Iftah; Coetzer, Rudi; Moore, Paul; Muñoz Zúñiga, José Fernando; Zellner, Maggie
ABSTRACT: As the knowledge derived from the dialog between neuroscience and psychoanalysis has provided relevant insights in topics such as affects, instincts, consciousness, memory, dreams, and many others, the question of its clinical applications has gained increasing interest. Using psychoanalytic techniques with neurological patients has gradually become a more common practice. However, integrating neuropsychoanalytic perspectives into work with non-neurological patients has represented a challenge that is being taken with caution. Case reports have been crucial for the development of psychoanalytic ideas. Based on this principle, progress in the clinical applications of neuropsychoanalytic knowledge can also benefit from case presentations. Nevertheless, the neuropsychoanalytic perspective entails added challenges. Hence, the editorial team of this journal gave a clinical writing workshop in February 2022. We present here brief essays that cover some of what we consider the most important topics involved in clinical writing in neuropsychoanalysis.